Algorithmic Probability and Friends. Bayesian Prediction and Artificial Intelligence: Papers from the Ray Solomonoff 85th Memorial Conference, Melbourne, VIC, Australia, November 30 - December 2, 2011 - Dowe, David L. (Lecture Notes in Computer Science, 2013)
This proceedings of the Ray Solomonoff 85th memorial conference, presents 35 papers on universal Bayesian prediction and artificial intelligence (machine learning). A tribute to Solomonoff's work, which influences modern data mining, econometrics and more.